2016
DOI: 10.5944/openpraxis.8.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in Massive Open Online Course (MOOC) Theses and Dissertations: Surfing the Tsunami Wave

Abstract: Massive Open Online Courses (MOOCs) have attracted a great deal of attention by higher education and private enterprises. MOOCs have evolved considerably since their emergence in 2008, all the while given rise to academic discussions on MOOC impact, design and reach. In an effort to understand MOOCs more comprehensively, this study analyzes theses and dissertations (N = 51) related to MOOCs and published between 2008 and 2015, identifying research trends from these academic documents. Theses and dissertations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 26 publications
(21 reference statements)
0
39
0
3
Order By: Relevance
“…They reported that the selected papers had a focus on students (83.6%), design (46.4%), context and impact (10.9%), and instructors (8.2%). Bozkurt, Özdamar Keskin, and de Waard (2016) reviewed 51 theses and dissertations published between 2008 and 2015. They identified that MOOCs are on the verge of the "plateau of productivity" as described in the Gartner Hype Cycle.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the selected papers had a focus on students (83.6%), design (46.4%), context and impact (10.9%), and instructors (8.2%). Bozkurt, Özdamar Keskin, and de Waard (2016) reviewed 51 theses and dissertations published between 2008 and 2015. They identified that MOOCs are on the verge of the "plateau of productivity" as described in the Gartner Hype Cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless PLAR methodologies are very much time and human resource consuming, alongside with the fact that in different countries methodologies vary. Besides, in case of MOOCs, the big numbers of learners make assessment problematic in terms of staffing (Chauhan, 2014) and often result in using automated machine assessment procedures.…”
Section: • Development Of New Open Knowledge Andmentioning
confidence: 99%
“…The rapid development and expansion of MOOCs resulted in a growing body of related research, for instance, the investigation of learning effectiveness, challenges of teaching and learning, motivation of both learners and teachers, learners' experience (Bozkurt, Keskin, & de Waard, 2016;Deng, Benckendorff, & Gannaway, 2019;Ebben & Murphy, 2014;Hew & Cheung, 2014;Liyanagunawardena & Williams, 2013;Raffaghelli, Cucchiara, & Persico, 2015;Veletsianos, Collier, & Schneider, 2015;Veletsianos & Shepherdson, 2015).…”
Section: Psychometrics Of Moocs: Measuring Learners' Proficiencymentioning
confidence: 99%